The Marginalist Principle in a Discrete Production Model Under Uncertain Demand: Comment - Whitin, T. M. (Quarterly Journal of Economics, 1974)
Journal Article The Marginalist Principle in a Discrete Production Model Under Uncertain Demand: Comment Get access T. M. Whitin T. M. Whitin Wesleyan University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 88, Issue 1, February 1974, Pages 139–140, https://doi.org/10.2307/1881801 Published: 01 February 1974